Land Bank Sebagai Solusi Inovatif Pembangunan Keberlanjutan: Mengatasi Perubahan Penggunaan Tanah di Kabupaten Sidoarjo - Rahmadhani, Shelvia Agustine; Fitrianto, Achmad Room (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
The rate of increase in population in Sidoarjo Regency continues to increase, and Sidoarjo Regency has medium and large industrial areas spread across 18 sub-districts. Of course, this will impact changes in land use in Sidoarjo Regency. In this way, the increasing demand for land in Sidoarjo Regency is not only for meeting residential needs but also for development in the industrial sector. The increase in demand for land will result in the availability of land becoming scarce, land market prices becoming unstable, and various problems arising. Seeing these problems, research was used to review whether the Land Bank concept could be a solution. The method used in this research is descriptive quantitative. The presence of the Land Bank is considered a way to make land management more productive. The study regarding Banklank in Sidoarjo Regency needs to be reviewed again by the local government so that land availability is balanced for the community. By implementing the Land Bank concept in Sidoarjo Regency, inefficient land use can be minimized, and the amount of land for the future can be maintained.